The Pretoria Statement on the Future of African Agriculture - Haggblade, Steven (International Food Policy Research Institute, 2004)
On December 1-3, 2003, the New Partnership for Africa's Development (NEPAD), Capacity Building International, Germany (InWent), the Technical Center for Agricultural and Rural Cooperation (CTA), and the International Food Policy Research Institute (IFPRI) assembled a group of experienced agricultural, trade, and finance specialists from government and the private sector and from across Africa to help review, summarize, and distill conclusions from the case studies of African successes. Together, these 70 specialists produced a shared statement of findings identifying priorities for future policy action necessary to trigger sustained agricultural growth in Africa. That shared statement, the Pretoria Statement, provides the best available summary of key lessons learned on how to scale up agricultural successes for the future -- from Text. In this brief, we learn that a series of successful episodes in African agriculture suggests two fundamental prerequisites for sustained agricultural growth (Good governance and Sustained funding for agricultural research extension) as well as a number of promising specific opportunities: Soil and water conservation; Replication of proven commodity-specific breeding and processing successes; Marketing and information systems; Vertical supply chains; and Regional cooperation in trade and agricultural technology.